Dog-bone inflation to salvage and redeploy a deformed, dislodged expandable stent in the external iliac artery. Issue 1 (January 2018) - Chung, Wen-Jung; Takeji, Yasuaki; Soga, Yoshimitsu; Ando, Kenji
Abstract: A 64-year-old man with a history of right external iliac artery stenosis after stenting with a self-expandable stent was admitted for repetitive in-stent restenosis (ISR). To treat ISR, we selected a balloon expandable stent (BES) that was prepared with negative suction before being inserted into the sheath. BES dislodged when the stent balloon was incompletely inflated and was simultaneously deformed in a funnel shape. When BES was retrieved using a short noncompliant balloon, it dislodged again because of an imbalanced proximal inflation of the balloon. We finally retrieved BES using a long noncompliant balloon and deployed it with dog-bone inflation without any additional devices. <Learning objective: To report an easy method for retrieving and redeploying a deformed, dislodged stent without using an additional device. Retrieving a relatively large peripheral stent that becomes deformed and dislodged is difficult and may require surgery. Balloon catheter retrieval is a useful strategy to salvage and redeploy the dislodged stent. However, a large size short noncompliant balloon catheter had the risk for dislodging the retrieved deformed stent again. To retrieve and salvage a deformed and dislodged stent, a long balloon and dog-bone inflation may be useful.>